2014
DOI: 10.1177/0009922814526979
|View full text |Cite
|
Sign up to set email alerts
|

Pediatricians’ Knowledge of Current Sports Concussion Legislation and Guidelines and Comfort With Sports Concussion Management

Abstract: General pediatricians are knowledgeable about concussions but most are not well aware of state concussion legislation and concussion consensus guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 25 publications
3
30
1
3
Order By: Relevance
“…This is inferred from 1 the low level of knowledge of common signs and symptoms of MTBIs and 2 the unfamiliarity or low familiarity of MDs (72%) and DCs (65%) with the latest consensus Zurich guidelines for evaluation and management of concussion. 21,38 These figures parallel Carl and Kinsella's 26 and Gordon et al's 35 findings of only 14% and 18% utilization of the Zurich guidelines by pediatricians. The Zurich guidelines also recommend improved methods of knowledge transfer, but addressed mainly the public's need.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This is inferred from 1 the low level of knowledge of common signs and symptoms of MTBIs and 2 the unfamiliarity or low familiarity of MDs (72%) and DCs (65%) with the latest consensus Zurich guidelines for evaluation and management of concussion. 21,38 These figures parallel Carl and Kinsella's 26 and Gordon et al's 35 findings of only 14% and 18% utilization of the Zurich guidelines by pediatricians. The Zurich guidelines also recommend improved methods of knowledge transfer, but addressed mainly the public's need.…”
Section: Discussionsupporting
confidence: 55%
“…26,[32][33][34][35][36] Specific questions were devised to provide insight into the baseline MTBI knowledge and clinical process of first-contact chiropractic and medical physicians in their evaluation and care of TBI patients. The questions were devised to reflect current concepts, guidelines, and clinical practice.…”
Section: Instrument Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past several years there have been numerous studies evaluating the knowledge and awareness of concussion among athletes, 4,[28][29][30][31][32][33][34] parents, 34,35 and coaches. 36,37 Studies have also addressed health care providers' knowledge and use of various concussion management practices, 14,[38][39][40][41][42][43][44][45] yet findings from our study highlight that knowledge-to-practice gaps may still exist.…”
Section: Concussion Education and Awarenessmentioning
confidence: 78%
“…Improve medical education about concussion. This includes better concussion education for students entering health professions but also improved education for health care professionals after graduation [10,11]. A study found that only 26.6 percent of general pediatricians were somewhat or very familiar with recently passed concussion legislation and that only 14.6 percent of general pediatricians used concussion consensus guidelines in their practice [12].…”
Section: Recommendationsmentioning
confidence: 99%